Mongolia : Southern Gobi Regional Environmental Assessment - World Bank (Washington, DC, 2017)
The primary objective of the Southern Gobi Regional Environmental Assessment (REA) is to provide guidance for sustainable management of environmental resources in the future development of the Southern Gobi Region (SGR), development that will be led by rapid expansion of mining. The REA defines two development scenarios-a base-case and a high case-and explores their direct and indirect impacts on the natural environment, taking into account the opportunities, constraints, and vulnerabilities of the Gobi natural systems; the individual and cumulative direct environmental impacts and potential indirect impacts of the planned development; and, at a general level, the institutional capacity to manage the impacts. The REA target audience includes government officials at central, regional, and local levels; private sector investors and the consultants who are engaged for project design and environmental impact assessment; development finance organizations; and Mongolian civil society. This report was discussed in draft form at stakeholder workshops held in Ulaanbaatar and Dalanzagdad in April 2009 and has been revised to reflect comments received. Thanks are due to all those who joined those discussions. The report draws on information from workshops held in Mongolia, in May, September, and October 2008, and a field mission to the Southern Gobi Region in November 2008. Other information was obtained from various mining companies in Mongolia including Ivanhoe mines Mongolia, Inc., and its consultant Eco Trade; Rio Tinto; Energy Resources LLC; and South Gobi Sands.